PENANAMAN NILAI ISLAM DALAM PEMBETUKAN ADAB ANAK USIA DINI MELALUI PEMBIASAAN HAFALAN ASMAUL HUSNAH DAN SURAT PENDEK DI BUSTANUL ATHFAL AISYIYAH GEMBUK I (BA AISYIYAH GEMBUK) - Ratna Sari, Fitri; Sanjaka Yekti (LPPM IAD Probolinggo, 2025)
This study focuses on understanding the instillation of Islamic values ​​in the formation of early childhood manners through the habit of memorizing Asmaul Husnah and Short Letters. In Bustanul Athfal Aisyiyah Gembuk I. The study used a qualitative method with a case study design. The results of the study showed that the habit of memorizing Asmaul Husnah and Short Letters can help children understand and internalize Islamic values, as well as improve their manners. This study recommends that the Asmaul Husnah and Short Letter memorization program can be integrated into the early childhood education curriculum. The increase in manners is reflected in the increase in scores on the manners indicator, such as saying hello, respecting parents, and avoiding bad behavior. In addition, the study also shows that the Asmaul Husnah and Short Letter memorization program can improve children's ability to memorize Asmaul Husnah and Short Letters. This study concludes that the habit of memorizing Asmaul Husnah and Short Letters can be an effective strategy in instilling Islamic values ​​in early childhood. Therefore, this study recommends that the program of memorizing Asmaul Husnah and Short Letters can be implemented into the early childhood education curriculum. Keywords: Instilling Islamic values, Formation of early childhood manners, Habit of memorizing Asmaul Husnah, Memorizing Short Letters